Peningkatan Kompetensi Guru Sekolah Menengah Kejuruan Melalui Implementasi Teknologi Pembelajaran 4.0 Berbasis LMS, Quizizz dan Google Classroom - Basorudin Basorudin; Antoni Pribadi; Dedi Leman; Luth Fimawahib (Journal of Social Responsibility Projects by Higher Education Forum, 2026)
The digital era demands that the education sector be able to adapt to the development of information technology, especially in the implementation of digital-based learning. However, the problem at SMK Negeri 1 Tambusai Utara is the still low understanding and application of 4.0 technology by teachers in the learning process, even tho supporting facilities such as the internet are well available. Therefore, a workshop on the implementation of 4.0 technology thru Learning Management Systems (LMS) such as Quizizz, Kahoot, and Google Classroom was conducted with the aim of enhancing teachers' competence in utilizing learning technology. The implementation method was carried out in two stages, namely the delivery of theoretical material and direct practice. The results of the activity show that all participants were able to understand and implement the LMS with a high level of success. Additionally, there was a shift in the learning pattern to become more interactive and student-centered, with an activity proportion of 70% students and 30% teachers. Thus, this workshop is effective in enhancing teachers' technological competencies and encouraging more engaging, effective, and efficient learning innovations.